Pengaruh Work Family Conflict Terhadap Pengembangan Karier - Diny Atrizka; Agung Maliki Herman; Jevika Luincky; Mona Elisa Putri Simanjuntak; Paskal Jevon Dachi (Psyche 165 Journal, 2021)
This study aims to look at the effect of work family conflict on career development. The subjects used in this study were 196 police officers in the North Sumatra Regional Police Directorate General of Criminal Investigation. The hypothesis proposed in this study states that the influence of work family conflict on career development, where work family conflict tends to undermine the career development of a police officer. Analysis of the data used in this study is Correlational Analysis through the help of SPSS 25 for windows. The results ofcorrelation analysis correlation values (r) of -0.416 with p = 0.000 (P <0.05). This research shows that the contribution of Adjust R Square given to work family conflict on career development is 16.9%, the remaining 83.1% is influenced by other factors. With this result it shows that there is a negative relationship between work family conflict and career development, where work family conflict significantly influences career development.